Application of the FP-Growth Algorithm in Analyzing Patterns and Layout of Foodstuffs - Ayu Padillah; Heru Satria Tambunan; Rizki Alfadillah Nasution (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
The purpose of this study was to determine the pattern and layout of the appropriate goods in Gono Stores using the FP-Growth Algorithm. Gono Store is a store that is engaged in the sale of food ingredients located in Nagori Dolok Kataran, Kec. Dolok Batu Nanggar. The arrangement of the layout of the goods greatly affects the volume of sales. However, in setting the layout at the Gono Store, there are some problems, namely the lack of knowledge of the shop owner in setting the layout . The FP-Growth algorithm is one of the alternative data mining algorithms that can be used to determine groups of data that often appear (Frequent item sets) in a set of data.The source of the research data used is by conducting observations and interviews at Gono Stores. From the overall results of the sales data 10 rules are formed with the minimum value limit of Support = 0.3and Confidence = 0,8. Its hoped that the result of this study will provide benefits in the form of information that can help shop owners in analyzing the pattern and layout of foodstuffs.